2020
DOI: 10.1038/s41598-020-77702-x
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid level and kidney function: a cross-sectional study of the Korean national health and nutrition examination survey (2016–2017)

Abstract: Kidney disease is expected to become the fifth leading cause of premature death globally by 2040. Uric acid level is a risk factor for kidney disease. The current study aims to investigate the association between uric acid levels and kidney function in the Korean population. The data of 11,042 participants of the 2016–2017 Korea National Health and Nutrition Examination Survey were analysed. The estimated glomerular filtration rate was calculated using the modification of diet in renal disease formula for Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Many studies have shown an association between IMC and high importance of major vascular risk factors for circulatory disorders: dyslipidemia and hypertension. The IMC thickness determines the individual severity of cardiovascular diseases [1,2].…”
Section: ключові словаmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown an association between IMC and high importance of major vascular risk factors for circulatory disorders: dyslipidemia and hypertension. The IMC thickness determines the individual severity of cardiovascular diseases [1,2].…”
Section: ключові словаmentioning
confidence: 99%
“…Hyperuricemia, which in some cases leads to the development of gout, is involved in the pathogenesis of hypertension and atherosclerosis [1]. Epidemiological studies revealed the relationship between hyperuricemia and atherosclerotic vascular disease, and serum uric acid (UA) levels, making it possible to predict cardiovascular events and mortality in women and men [2].…”
Section: ключові словаmentioning
confidence: 99%
“…(Continues) males and females, the results showed a linear increase as the age at first use of alcohol decreased. In male group, 15 or under OR was 2.50, 95% CI (1.97-3.17),16-18 OR 1.82, 95% CI (1.46-2.27), 19-23 OR 1.29, 95% CI (1.04-1.60), and putting those who first started drinking alcohol after they became age 24. In female group, 15 or under group OR was 1.66, 95% CI (1.18-2.33), 16-18 OR 1.61, 95% CI (1.23-2.11), 19-23 OR 1.04, 95% CI (0.81-1.…”
mentioning
confidence: 93%
“…Due to the feature of cross-sectional study, overlapping individuals by year were not removed, but they were regarded as another individual study participant. The data from these surveys are used to monitor and estimate the prevalence of chronic diseases and citizens'health in the South Korean population 16,17.…”
mentioning
confidence: 99%
“…Although uric acid is an endogenous antioxidant, studies link high serum uric acid levels with a number of conditions, including hypertension and cardiovascular disease, as well as metabolic syndrome and diabetes [ 3 , 4 , 5 , 6 ]. A large Korean study on more than 11,000 participants found a dose–response relationship between uric acid levels and decreased kidney function in both men and women [ 7 ]. The causal relationship and mechanisms connecting gout, hyperuricemia, and various comorbidities are complex, and not fully understood, with contradicting reports and studies [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%